Analisis Pencemaran Tanah di Desa Gembol Penjawaran Banjarnegara - Syaifullah, Yogi; Wati, Fenia Taasa (MASALIQ, 2023)
This study aims to analyze the soil pollution that occurred in Gembol Village, Pejawaran District, Wonosobo Regency. This type of research is qualitative research, with a descriptive study research design. The data collection technique used in this study used Observation Studies, namely by interviewing one of the potato farmers in Gembol Village and from books, journals, research results, theses, dissertations, newspapers and the internet. In this study, researchers used books, journals and the internet. The results of this study found that soil pollution that occurred in Gembol Village resulted from the continuous use of chemical fertilizers in the potato planting process. The use of chemical fertilizers results in a decrease in soil quality so that the yields obtained by farmers also decrease with each harvest. The results of the data analysis showed that the potato farmers in Gembol Village experienced a decrease in the amount they harvested by 100 kg every last 2-3 years.